PERENCANAAN STRUKTUR BANGUNAN BAWAH ABUTMENT JEMBATAN DESA SEKERAT KECAMATAN BENGALON KABUPATEN KUTAI TIMUR - ROHADI, SLAMET (KURVA S JURNAL MAHASISWA, 2017)
The bridge is a part of a highway that is functioning to connect a brokenroad due to obstacles such as rivers, lakes, valleys, ravines and others. In theplanning and work of the bridge Under the Structure Planning can not be ignored.Part of this bridge structure located at the bottom is crucial for the strength andsecurity of buildings on it. And for direct link between upper bridge structure withunder bridge structure is